Influence of substrate temperature on the chemical, microstructural and optical properties of spray deposited CH3NH3PbI3 perovskite thin films - Gabriel Bartholazzi; Robson Pacheco Pereira; Andreza Menezes Lima; Wagner Anacleto Pinheiro; Leila Rosa Cruz (Journal of Materials Research and Technology, 2020)
Methylammonium lead iodide (CH3NH3PbI3) perovskite has been proposed as a key component of thin film solar cells. In this work, the influence of substrate temperature on the properties of spray deposited CH3NH3PbI3 thin films was investigated. The main purpose of this work was to determine the best conditions to deposit and crystallize CH3NH3PbI3 perovskite thin films in a single step. An automatic spray system was used for depositing a solution of lead iodide and methylammonium iodide onto heated substrates under ambient conditions for just one second. After deposition the samples were held at the same temperature for 30 s. The substrate temperature varied from 60 °C to 140 °C. Substrate temperatures in the low range (60 °C–80 °C) led to films with needle-like or dendritic grains, extra phases, and poor coverage due to the low solvent evaporation rate, while depositions above 120 °C led to thermal decomposition of the film. The best results were obtained for substrate temperatures of 100 °C and 120 °C, which produced dense perovskite films with large equiaxed grains and good coverage. The transmittance spectra of these films showed the perovskite characteristic absorption edge at 780 nm. In addition, the Fourier-transform infrared spectra did not show any peaks associated with the solvent, confirming its evaporation and indicating that a 31 s overall processing time is enough to achieve a full perovskite crystallization.